Congenital syphilis in Santa Inês - MA: epidemiological characterization (Research, Society and Development, 2020)
Syphilis is caused by a bacterium called Treponema pallidum, genus Treponema, of the Treponemataceae family, characterized by being systemic, chronic evolution and transmission through sexual or maternal-fetal intercourse. Syphilis is a sexually transmitted disease (acquired syphilis) and vertically (congenital syphilis) transmitted from the mother's placenta to the fetus. The study aimed to establish the prevalence of congenital syphilis, tracing an epidemiological profile through the cases reported in the city of Santa Inês, Maranhão. This is a retrospective, exploratory, descriptive and quantitative cohort developed in the municipality of Santa Inês, State of Maranhão, from January 2010 to December 2018. There was a growing trend in all the years analyzed. with a substantial increase from 2017, mainly in the Northeast and Maranhão state, already in the municipality of Santa Inês in 2013, there was a considerable decrease in cases with an increase in the subsequent year and with a higher incidence in the year. 2018 with a greater number of cases than the cases of the northeast of Maranhão state. Thus, Based on the data presented, the incidence of congenital syphilis in the municipality of Santa Inês can be characterized through the epidemiological analysis of the temporal cutoff of 08 years.